Geographic evidence for source–sink dynamics in deep‐sea neogastropods of the eastern North Atlantic: an approach using nested analysis. Issue 4 (1st November 2012) - Brault, Solange; Stuart, Carol T.; Wagstaff, Martine C.; Rex, Michael A.
Abstract Aim We conduct a nested analysis of bathymetric distributions in neogastropods to test the hypothesis that bathyal and abyssal populations represent a source–sink system. Abyssal assemblages are predicted to be significantly nested subsets of bathyal assemblages, and to be characterized by low density, which drives extinction, and a high incidence of species with larval dispersal for continued immigration to maintain diversity. Location Bathyal and abyssal regions of the eastern North Atlantic Ocean. Methods We used published indices of beta diversity to distinguish the components of species dissimilarity among sites that are caused by turnover and nestedness. We used BINMATNEST and its most conservative null model to test specifically for nestedness along a depth gradient. Results Both turnover and nestedness affect beta diversity, but dissimilarity due to turnover predominates at depths of less than 3000 m, and dissimilarity due to nestedness at depths greater than 3000 m. Nestedness increases significantly down‐slope at depths greater than 1000 m. The rank order of nestedness is significantly predicted by macrofaunal density and by the proportion of neogastropod species with dispersing larvae. Main conclusions Bathymetric patterns of beta diversity in the deep‐sea benthos have been interpreted largely as a consequence of species turnover. Our results indicate that beta diversity in neogastropods is composed of two separate processes, turnover and nestedness, and that their relative importance changes with depth. Dissimilarity among sites due to nestedness, coupled with information on standing stock and life history, suggests that at least part of the abyssal neogastropod assemblage is maintained by source–sink dynamics.